Perbandingan Algoritma Penjadwalan Symbiotic Organisms Search dan Earliest Due Date: Studi Kasus di PT Citra Indah Abadi Jaya - Davin Hariyanto; Tanti Octavia; Iwan Halim Sahputra (Jurnal Titra, 2020)
PT Citra Indah Abadi Jaya is a service company engaged in the powder coatings of aluminum and metal. The problem that occurs in companies is that there is lateness in order completion. This lateness was caused by company schedulling based on the estimation of the Production Department. Therefore, a production schedulling algorithm is needed that can minimize the maximum lateness in the company. The algorithm that will be used in this research is the Symbiotic Organisms Search (SOS) and Earliest Due Date (EDD) algorithms. The SOS and EDD algorithm programs are run with Excel VBA. The eco size of the SOS algorithm is 50 with 20 replications. The results of the proposed best algorithm will be compared with schedulling the company's actual conditions. It is expected that the proposed schedulling algorithm can meet the needs of the company.